study and scFv design against Bm17DIII gene product from Brugia malay: from dry lab to wet lab. - Choong , Yee Siew (Universiti Sains Malaysia, 2014)

(untitled)
The continuing endemicity of lymphatic filariasis in developing and under-developed countries emphasizes the need for a rapid, affordable and accessible diagnostic test for disease management.